2019
DOI: 10.1097/bpo.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Brachial Plexus Birth Palsy in the United States: Declining Incidence and Evolving Risk Factors

Abstract: Level III-case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 24 publications
4
54
0
1
Order By: Relevance
“…However, another study group of DeFrancesco et al reported the presence of compressive and traction forces as seen with shoulder dystocia as one of the causes which has been shown as the strongest risk factor. 5 Memo et al stated that BPBP can be caused due to fetopelvic disproportion, which would lead to shoulder dystocia. 6 Majority of the respondents felt that these injuries can be prevented by the use of birth simulators.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study group of DeFrancesco et al reported the presence of compressive and traction forces as seen with shoulder dystocia as one of the causes which has been shown as the strongest risk factor. 5 Memo et al stated that BPBP can be caused due to fetopelvic disproportion, which would lead to shoulder dystocia. 6 Majority of the respondents felt that these injuries can be prevented by the use of birth simulators.…”
Section: Discussionmentioning
confidence: 99%
“…OBPP is a complication that occurs during childbirth and the frequency of the disease in the general population is 1-3 per 1000 live births. This rate can be compared to other disorders that occur during childbirth or during the early and later stages of a child's life such as Down's Syndrome and Cerebral Palsy 2,3 . Recovery is also reported but there is a variation to the specific rate (30-90%).…”
Section: Introductionmentioning
confidence: 99%
“…La lesión del plexo braquial es definida como la debilidad flácida de la extremidad superior que ocurre como resultado de la tracción durante el nacimiento. 1 La incidencia reportada en varios países varía de entre 0.38 a 5.1 por 1,000 nacidos vivos; en Estados Unidos ha sido demostrada en 1.51 por cada 1,000 habitantes en datos obtenidos de 1997 a 2003. 2 A medida que aumenta la incidencia de cesárea disminuye la incidencia de lesión del plexo braquial, el factor de riesgo más grande es la distocia de hombros, lo que significa que un niño tiene una probabilidad de 10.4% de sufrir una lesión del plexo si ocurre esta complicación durante el parto.…”
Section: Introductionunclassified